The Mas receptor mediates modulation of insulin signaling by angiotensin-(1-7) - Muñoz, Marina Cecilia (2012)
Angiotensin (Ang)-(1-7) stimulates proteins belonging to the insulin signaling pathway and ameliorates the Ang II negative effects at this level. However, up to date, receptors involved and mechanisms behind these observations remain unknown. Accordingly, in the present study, we explored the in vivo effects of antagonism of the Ang-(1-7) specific Mas receptor on insulin signal transduction in rat insulin-target tissues. We evaluated the acute modulation of insulin-stimulated phosphorylation of Akt, GSK-3β (Glycogen synthase kinase-3β) and AS160 (Akt substrate of 160kDa) by Ang-(1-7) and/or Ang II in the presence and absence of the selective Mas receptor antagonist A-779 in insulin-target tissues of normal rats. Also using A-779, we determined whether the Mas receptor mediates the improvement of insulin sensitivity exerted by chronic Ang-(1-7) treatment in fructose-fed rats (FFR), a model of insulin resistance, dyslipidemia and mild hypertension. The two major findings of the present work are as follows; 1) Ang-(1-7) attenuates acute Ang II-mediated inhibition of insulin signaling components in normal rats via a Mas receptor-dependent mechanism; and 2). The Mas receptor appears to be involved in beneficial effects of Ang-(1-7) on the phosphorylation of crucial insulin signaling mediators (Akt, GSK-3β and AS160), in liver, skeletal muscle and adipose tissue of FFR. These results shed light into the mechanism by which Ang-(1-7) exerts its positive physiological modulation of insulin actions in classical metabolic tissues and reinforces the central role of Akt in these effects.